Social Media and Senior Citizens - Johnson , R. David (Social Innovations Journal, 2013)
According to a study conducted by the Pew Internet and American Life Project, approximately 87% of senior citizens use online search engines such as Google, and a study conducted by the Nielsen Company found that 88.6% of senior citizens use the Internet to check their e-mail (Yang 2012). A recent study by Socialbakers found that the average age of a Facebook user changed from 29.53 in 2010 to 30.11 in 2013 as older people become more computer and social media-literate (Allen 2013). Such findings help substantiate the fact that senior citizens are more active with social media than previously assumed. There are a few reasons why more senior citizens are using social media than expected. The findings from the study are likely because those who could afford a computer were adults in their forties when the Internet began to gain its popularity in the mid-1990s (Crouch 2011). The average price for a computer in the 1990s was approximately $2,000.00 (Qasim, 2011). This is more than triple the cost of a basic personal computer today. Those who were able to afford a personal computer in the 1990s were presumably professionals, well-educated and in higher-income brackets (Crouch). These adults are now in their 50s and 60s, are still active and well-educated with the Internet and social media. The following data from the Pew Internet and American Life Project illustrates the age ranges of individuals who use the Internet, social media sites and e-mail technology: